2017
DOI: 10.1186/s12884-017-1546-7
|View full text |Cite
|
Sign up to set email alerts
|

Do mobile clinics provide high-quality antenatal care? A comparison of care delivery, knowledge outcomes and perception of quality of care between fixed and mobile clinics in central Haiti

Abstract: BackgroundAntenatal care (ANC) is an important health service for women in developing countries, with numerous proven benefits. Global coverage of ANC has steadily increased over the past 30 years, in part due to increased community-based outreach. However, commensurate improvements in health outcomes such as reductions in the prevalence of maternal anemia and infants born small-for-gestational age have not been achieved, even with increased coverage, indicating that quality of care may be inadequate. Mobile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…1). Five papers (describing five distinct studies) met the inclusion criteria and were included in the synthesis; these are summarised in Table 1 [14][15][16][17][18]. Papers were screened out following full-text assessment owing to: a lack of empirical data, the paper reported on an out of scope modality, and/or the context was a non-humanitarian setting.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Five papers (describing five distinct studies) met the inclusion criteria and were included in the synthesis; these are summarised in Table 1 [14][15][16][17][18]. Papers were screened out following full-text assessment owing to: a lack of empirical data, the paper reported on an out of scope modality, and/or the context was a non-humanitarian setting.…”
Section: Resultsmentioning
confidence: 99%
“…The five included studies reported on mobile clinic interventions focusing on non-communicable diseases [14], mental health [15], sexual and reproductive health [18], and multiple primary health services [16,17] in Afghanistan [17], the Democratic Republic of the Congo (DRC) [16], Haiti [15,18], and the Occupied Palestinian Territories (OPT) [14]. The study designs employed included: a quasiexperimental longitudinal study [14], two retrospective longitudinal studies [15,17], a cross-sectional survey [9], and one self-described 'case study' which includes some elements of programme evaluation [16].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations